Industrial Structure, Executives' Pay And Myopic Risk Taking. - Thanassoulis, J (Department of Economics (University of Oxford), 2011)
This study outlines a new theory linking industrial structure to optimal employment contracts and value reducing risk taking. Firms hire their executives using optimal contracts derived within a competitive labour market. To motivate effort firms must use some variable remuneration. Such remuneration introduces a myopic risk taking problem: an executive would wish to inflate early expected earnings at some risk to future profits. To manage this some bonus pay is deferred. Convergence in size amongst the largest firms makes the cost of managing the myopic risk taking problem grow faster than the cost of managing the moral hazard problem. Eventually the optimal contract jumps from one achieving zero myopic risk taking to one tolerating the possibility of myopic risk taking. Under some conditions the industry partititions: the largest firms hire executives on contracts tolerant of myopic risk taking, smaller firms ensure myopia is ruled out.